Analisis Yuridis Sosiologis Pelaksanaan Pengendalian Aksi Massa di Stadion Kanjuruhan Kepanjen - Enggalani, Budiarso; Suratman, Teguh (Postgraduate University of Merdeka Malang, 2024)
The tragedy that occurred at Kanjuruhan Stadium, Malang Regency on October 1, 2022, became a widely spotlighted event. On that day, a football match between Arema and Persebaya ended in riots that resulted in 131 deaths and hundreds of injuries. A case study of the Kanjuruhan Stadium tragedy is important to analyze whether the mass control strategies implemented by the Indonesian National Police (Polri) were in line with the established regulations and the police code of ethics that uphold human rights. Based on this background, the author will analyze firstly; what were the obstacles faced by the Riot Control Unit (PHH) of the Brimob unit of Polri in managing the mass action at Kanjuruhan Stadium, Malang Regency on October 1, 2022, in reference to Perkap NRI No. 1 of 2009 and Protap No. 1/X/2010, and secondly; how is the juridical-sociological analysis of the standard strategies of the Riot Control Unit (PHH) of the Brimob unit of Polri in managing mass actions according to Perkap NRI No. 1 of 2009 and Protap No. 1/X/2010. In this research, the author employs the Empirical Juridical Analysis method. Based on the results of this study, it can be concluded that the obstacles faced by the Riot Control Unit (PHH) of the Brimob unit of Polri in managing the mass action at Kanjuruhan Stadium, Malang Regency, are hindered by a paradigm, particularly among law enforcement officers, that views the incident as a disaster. The legal process of the Kanjuruhan tragedy did not receive extensive media coverage. The supervision by the DPR's Commission III over its partners such as Polri and the Ministry of Law and Human Rights has not been carried out in detail. The Standard Strategy for Mass Control by the Riot Control Unit (PHH) of the Brimob unit of Polri According to the Applicable Provisions. The implementation of the mass control strategy by the Riot Control Unit (PHH) of the Brimob unit of Polri at Kanjuruhan Stadium, Malang on October 1, 2022, according to the applicable provisions, includes pre-emptive measures, which are initial actions taken by the police in issuing warnings and approaching riot groups to maintain order. Preventive measures are efforts carried out by the police in performing their duties according to standard procedures (Protap). Repressive measures are the last actions taken by the police when the riot has become uncontrollable.